Śmierć i ostateczne przeznaczenie człowieka w ujęciu Maksyma Wyznawcy - Kochańczyk-Bonińska, Karolina (Vox Patrum, 2010)
The article presents how Maximus as Christian and philosopher understands death and eternal life. First of all, Confessor connects death with original sin and separation from God. In another meaning death is for him separation of body and soul, so that our life becomes continues preparation for death. Another important problem presented is if and how different elements of human being (intellect, soul and body) would cooperate in eternal life. Author presents Maximus’ attitude towards the conception of apocatastasis and shows that there is no place for such conception in Maxim’s writings. The last important problem presented in the article is deification understood as union with God (not only human beings but whole creation united with Creator) and Sabbath, which is the end of all movement and rest in God.